The Distinctive Evolution of orfX Clostridium parabotulinum Strains and Their Botulinum Neurotoxin Type A and F Gene Clusters Is Influenced by Environmental Factors and Gene Interactions via Mobile Genetic Elements - Smith, Theresa J.; Williamson, Charles H. D.; Hill, Karen K.; Johnson, Shannon L.; Xie, Gary; Anniballi, Fabrizio; Auricchio, Bruna; Fernández, Rafael A.; Caballero, Patricia A.; Keim, Paul; Sahl, Jason W. (Frontiers in Microbiology, 2021)
Of the seven currently known botulinum neurotoxin-producing species of Clostridium, C. parabotulinum, or C. botulinum Group I, is the species associated with the majority of human botulism cases worldwide. Phylogenetic analysis of these bacteria reveals a diverse species with multiple genomic clades. The neurotoxins they produce are also diverse, with over 20 subtypes currently represented. The existence of different bont genes within very similar genomes and of the same bont genes/gene clusters within different bacterial variants/species indicates that they have evolved independently. The neurotoxin genes are associated with one of two toxin gene cluster types containing either hemagglutinin (ha) genes or orfX genes. These genes may be located within the chromosome or extrachromosomal elements such as large plasmids. Although BoNT-producing C parabotulinum bacteria are distributed globally, they are more ubiquitous in certain specific geographic regions. Notably, northern hemisphere strains primarily contain ha gene clusters while southern hemisphere strains have a preponderance of orfX gene clusters. OrfX C. parabotulinum strains constitute a subset of this species that contain highly conserved bont gene clusters having a diverse range of bont genes. While much has been written about strains with ha gene clusters, less attention has been devoted to those with orfX gene clusters. The recent sequencing of 28 orfX C. parabotulinum strains and the availability of an additional 91 strains for analysis provides an opportunity to compare genomic relationships and identify unique toxin gene cluster characteristics and locations within this species subset in depth. The mechanisms behind the independent processes of bacteria evolution and generation of toxin diversity are explored through the examination of bacterial relationships relating to source locations and evidence of horizontal transfer of genetic material among different bacterial variants, particularly concerning bont gene clusters. Analysis of the content and locations of the bont gene clusters offers insights into common mechanisms of genetic transfer, chromosomal integration, and development of diversity among these genes.